Islamic Economics Thoughts and Schools - Mayang Bundo; Afriyanti Afriyanti; Mulyadi Muslim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Islamic economics developed from the history of Muslim thinkers in the past. They see that in the order of community life as a whole there is no separation of scientific disciplines, so they see that in this case there is a need for policies that regulate the community's economy. This can be used as a tool to see why economics has not been discovered as a separate discipline in the past. In addition to knowing the relevance of whether Islamic economics is a combination of two economic systems or does it stand alone and is an alternative economy in the current era, it is necessary to study the thoughts and schools of Islamic economics.